On the Notions of ‘Examination’ and ‘Forensic Examination’ According to the Law of the Republic of Kazakhstan - AUBAKIROVA, Anna Aleksandrovna; ALIMOVA, Elvira Abdikapbarovna; UMIRBAYEVA, Zauresh Abilgozhanovna; ALAYEVA, Gulnaz Tursunovna; DAUBASSOVA, Sulushash Shinzhrhanovna (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
The paper deals with the notions of ‘examination’ and ‘forensic examination’ subject to Kazakh legislation, the characteristics of these notions’ content as significant in state’s activities is given, that said their distinctive features indicating the need for their differentiation are shown. The object of the research in the article of criminal procedure relations connected with the appointment, the production of forensic examinations, analysis, evaluation and use of their results in the criminal proceedings. The subject of research articles is the legal norms of the Russian (the modern and pre-existing) legislation governing the appointment and manufacture of judicial examination. It is shown that the appointment and examination in the trial court takes place in conditions of transparency, competitiveness, orality and immediacy. It was found that the appointment of judicial examination in judicial stages of self-regulation needed to be. The authors determined the need to provide for the appointment of the examination during the preliminary hearing. The authors also argue that we must distinguish between the following situations related to the appointment of the examination at the stage of preparation of the case for the court hearing and the trial. It is shown that, depending on these situations provided certain judges algorithm of actions on the issues under investigation.